The changing brain: Neuroscience and the enduring import of everyday experience. (October 2015) - Pickersgill, Martyn; Martin, Paul; Cunningham-Burley, Sarah
Discourses of 'neuroplasticity' have become increasingly apparent in the neurosciences and wider society. These connect with broader narratives about the 'changing brain' throughout the life-course. Here, we explore their presence in the talk of a range of publics. Their presence is indicative of how novel neuroscience is accepted, or not, by our participants. In particular, we suggest that any acceptance of the science relates to their personal and/or professional experiences of change (to their own or others' subjectivities) rather than to some intrinsic and widely-held significance of scientific concepts per se. Accordingly, we also submit that it is in part through the congruence of some neuroscientific claims to everyday experiences and perspectives that the former are rendered legible and salient. In this respect, 'lay' knowledge has considerable import for the wider cultural authorisation of that of 'experts'.